On two new species of the shrimp genus Salmoneus Holthuis, 1955 (Decapoda, Caridea, Alpheidae) from the tropical eastern Pacific - Anker, Arthur; Lazarus, Juan Felipe (Zootaxa, 2015)
The present study deals two new alpheid shrimp species from the transisthmian Salmoneus ortmanni (Rankin, 1898) complex. Salmoneus alvarezi sp. nov. is described based on materials collected in Bahía Málaga, Colombia, and Punta Morales, Costa Rica, and is closely related to the western Atlantic S. ortmanni and S. wehrtmanni Anker, 2011. Salmoneus malagensis sp. nov. is described based on specimens from Bahía Málaga, Colombia, and beyond any doubts represents the eastern Pacific sister species of the western Atlantic S. carvachoi Anker, 2007. The two new species can be easily distinguished from each other by a number of morphological characters and colouration, and in addition appear to be ecologically separated. All previous records of S. ortmanni from the eastern Pacific are reassigned, some tentatively, to S. alvarezi sp. nov. based on description, illustrations or ecological data.